A comparative analysis of risk factors for stroke in blacks and whites: The Atherosclerosis Risk in Communities study - Huxley, Rachel; Bell, E.; Lutsey, P.; Bushnell, C.; Shahar, E.; Rosamond, W.; Gottesman, R.; Folsom, A. (2014)
© 2013 Taylor and Francis. Objective. Previous studies have speculated that the higher stroke incidence rate (IR) in blacks compared with whites may be due, in part, to stroke risk factors exerting a more adverse effect among blacks than whites. To determine whether such racial differences exist we compared the prospective associations between novel, traditional, and emerging stroke risk factors in blacks and whites.Design. Baseline characteristics on risk factor levels were obtained on 15,407 participants from the Atherosclerosis Risk in Communities Study. Stroke incidence was ascertained from 1987 to 2008. Adjusted Cox proportional hazard models were used to compute hazard ratios (HRs) and their 95% confidence intervals (CIs) for stroke in relation to stroke risk factor levels stratified by race.Results. During follow-up, 988 stroke events occurred: blacks had higher stroke incident rates compared with whites with the greatest difference in those aged <60 years: 4.34, 3.24, 1.20, and 0.84 per 1000 person-years, in black men, black women, white men, and white women, respectively. Associations between risk factors with incident stroke were similar in blacks and whites excluding diabetes which was more strongly associated with the risk of stroke in blacks than in whites: HR 2.54 (95% CI: 2.03-3.18) versus 1.74 (1.37-2.21), respectively; p for race interaction = 0.02.Conclusions. At all ages, blacks are at a considerably higher risk of incident stroke compared with whites, although the effect is most marked in younger age groups. This is most likely due to blacks having a greater burden of stroke risk factors rather than there being any substantial race differences in the associations between risk factors and stroke outcomes.